A self-determination theory perspective of teacher motivation and self-directed learning skills to enhance academic performance in selected lower quintile primary schools - Geduld, Bernadette (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
Learners from low socioeconomic contexts are often instructed by poorly trained and qualified teachers, causing them to be often poorly motivated for their tasks, which is detrimental to learner performance. This study explored (a) factors that influenced the motivation and teaching behaviour of lower quintile schoolteachers with a view to enhancing learner academic performance and (b) the self-directed learning skills reflected in teachers’ teaching behaviour that enhanced learner academic performance. This study followed a basic qualitative study method in which semi-structured interviews were conducted with 12 purposively selected teachers from lower quintile primary schools. The participants listed a supportive school environment, collegiality, organisations, and community projects that support education in small towns as extrinsically motivating contextual factors. Furthermore, the reciprocal influences of communities with a low socioeconomic status, poor parental involvement, ill learner discipline, and limited support from the Department of Basic Education in providing specialised psychological and remedial support for struggling learners were factors that had a negative bearing on the participants’ relatedness, competence and autonomy. Future research is needed to explore the drivers of motivation in lower quintile schoolteachers by using a greater sample of participants from primary and secondary schools.
Journal article published in African Perspectives of Research in Teaching & Learning (APORTAL) Vol 7 (1) (2023)
Keywords: Motivation; Lower quintile schools; Self-determination theory; Self-directed learning; Teachers; Motivation in education; Academic achievement; Self-managed learning; Education, Primary